TOURISM MANAGERS COMPETENCY A CRITICAL EVALUATION ON KERALA TOURISM - Pradeep Kumar C; Sakthivel, R and Hareesh N. Ramanathan (Journal of Strategic Human Resource Management, 2014)
The robust growth of tourism industry was quite satisfactory even in the toughest macroeconomic environment across the globe. Nearly 85 percent countries have reported positive growth and out of this 33 percent have recorded double digit growth. The travel and tourism industry holds tremendous potential for contributing to the Indian economy also. The Government of Kerala, by way of an aggressive marketing strategy has envisaged the achievement of a yearly growth rate of fifteen percent on foreign tourist arrivals and seven percent on domestic tourist arrivals respectively. Despite the sluggishness in targeted market, tourism operators are putting all efforts to attract tourists with innovative marketing techniques to achieve the envisaged target. Though the Government of Kerala has taken so many initiatives to reduce the gap in the man power requirement, this could not be achieved. Attrition rate of this industry has not only been causing a dent on the performance of existing staff but it has an adverse effect also in the tourism sector as a whole. Keeping this in view, a questionnaire survey was conducted among the professionals associated with tourism industry to find out the competency needs of tourism managers who can perform and meet the target in this dynamic environment. The data was subjected to statistical analysis and found the various generic and functional competencies that are required for managing the tourism industry effectively.